Designing and analysing parallel control for multifeed ternary systems (2010)
This paper explores a parallel control structure for improving the behaviour of a chemical plant having recycling and multi- ple feed streams; a ternary system is taken as an example,having an A + B → C second-order irreversible reaction. Material recycling dynamics can induce the so-called snowball effect in the presence of disturbance in the feed stream. The snowball effect can be prevented by distributing load through the parallel control scheme. A control structure was thus pro- posed where product composition was regulated by means of simultaneous feedback manipulation of final column vapour boilup rate and reactor temperature. An extension was made for one reactor, one distillation column and recycle stream configuration. Nonlinear simulations showed that effective composition control could be obtained with moderate vapour boilup control efforts.